Investigating the interactions between tumour cells and the non-tumour cellular community in colorectal cancer - Susanti, Susanti (2021)
Colorectal cancer (CRC) is one of the leading causes of cancer-related mortality. It is a heterogeneous disease and several different classifications for CRC have been developed over the years. The most recent classification has identified 4 tumour groups which has been called “Consensus Molecular Subtypes (CMS)”. As well as molecular differences in the epithelium, the CMS classification also identifies distinguishing features in the stroma. Thus, tumours belonging to CMS1 have hypermutation in the cancer epithelium and are characterized by a prominent lymphocytic infiltrate. In contrast, tumours belonging to CMS4 have activation of the TGF-b signalling pathway and a dense fibrous stroma. Since CRC arises as a consequence of gene mutation and these mutations only occur in the epithelial cells, it follows that signalling from the epithelial cells may influence the population profile of the cells in the stroma (i.e. the cancer community). This study hypothesized that (i) the cellular community in CRC is non-random and is dictated by signals from the epithelium and (ii) that, in turn, the cellular community can influence tumour kinetics.